V PENGUATAN KELEMBAGAAN DALAM PEMBINAAN VETERAN: STUDI KOORDINASI ANTARA KODAM DAN DIREKTORAT VETERAN KEMENTERIAN PERTAHANAN - Indra Kritian; Tati Herlia (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2025)
Veteran development has a strategic role in maintaining welfare and respecting the service that has been given to the country. Law Number 15 of 2012 concerning Veterans of the Republic of Indonesia is the main legal basis for managing the rights and development of veterans. However, its implementation still faces various obstacles, such as a lack of synergy between the Kodam as the implementer in the field and the Veterans Directorate of the Ministry of Defense as the supervisor. This research aims to evaluate institutional coordination mechanisms in veteran development and provide recommendations for strengthening effective coordination. Using a qualitative approach, this research analyzes primary data from in-depth interviews and secondary data in the form of related policy documents. The findings show that the main obstacles to implementation are suboptimal coordination, limited human resources, and the complexity of the administrative process. To overcome this, it is necessary to strengthen coordination mechanisms through additional regulations, increase institutional capacity, and digitize administrative processes. It is hoped that stronger synergy between the Regional Military Command and the Veterans Directorate can increase the effectiveness of development and ensure that veterans' rights are implemented well. This research makes an important contribution to the development of institutional governance in developing veterans that is more inclusive and efficient by building a Kemhan regional office in each Kodam as an extension in carrying out Veterans administration and development.